Smokers' Neurological Responses to Novel and Repeated Health Warning Labels (HWLs) From Cigarette Packages - Fridriksson, Johann F.; Rorden, Chris; Newman-Norlund, Roger D.; Froeliger, Brett; Thrasher, James F. (Frontiers in Psychiatry, 2018)
The Family Smoking Prevention and Tobacco Control Act was signed into law in 2009 and gave the U.S. Food and Drug Administration (FDA) the authority to implement pictorial health warning labels (HWLs) on cigarette packages. The extant literature suggests graphic HWL’s—those depicting bodily damage due to smoking—are the most effective for producing changes in affect, cognition and smoking behavior. However, little is known about the effects of repeated presentation of graphic HWL’s on the aforementioned processes. Therefore, the goal of this study was to examine neural and behavioral responses to graphic HWL’s and evaluate whether the repeated presentation of graphic HWL’s leads to repetition suppression (RS) / habitation. Smokers (N = 16) performed an event-related HWL cue task while blood oxygen level dependent (BOLD) signal was collected during a functional magnetic resonance imaging (fMRI) experimental session. Consistent with the extant literature, graphic HWL’s, as compared to scrambled images, elicited increased BOLD response in brain regions involved in self-referential and emotion processing. Importantly, BOLD response at sites in this network diminished during repeated presentation of the same HWL. These findings suggest that while novel graphic HWL’s may have a significant effect on smokers’ brain activity, repeated presentation may lead to habituation and thus limit their potential impact on changing behavior. Future neuroimaging investigations of the brain’s response to HWLs should take habituation into consideration in order to better understand HWL characteristics/qualities that maximize the strength of their initial effect on the brain as well as their ability to produce an effect on behavior after multiple presentations akin to those encountered by smokers in daily life.